East Asian Arch Psychiatry 2022
DOI: 10.12809/eaap20104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Suicidal Ideation and Suicide Attempt in People With Human Immunodeficiency Virus in Africa: a Systematic Review

Abstract: Background: People with human immunodeficiency virus (HIV) are at higher risk of suicidal ideation and suicide attempts. We reviewed the literature for the prevalence and determinants of suicidal ideation and suicide attempt in people with HIV in Africa. Methods: The PubMed, Scopus, and Google scholar were searched for original studies published in peerreviewed journals in English language between January 2015 to July 2020, using the key words: 'suicidal behavior', 'suicidal attempt', 'suicidal ideation', 'HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Suicidal ideation and suicide attempts can exist in all stages of the HIV course, and the prevalence is elevated in both males and females [52]. A recent systematic review reported that female gender was a risk factor for suicidal ideation and suicide attempts among people living with HIV [52], which was in line with the results of our meta-analysis. One possible interpretation is that females are more likely to internalise stressful occurrences and experience psychological abuse [54], whereas males tend to express or act them out [55].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Suicidal ideation and suicide attempts can exist in all stages of the HIV course, and the prevalence is elevated in both males and females [52]. A recent systematic review reported that female gender was a risk factor for suicidal ideation and suicide attempts among people living with HIV [52], which was in line with the results of our meta-analysis. One possible interpretation is that females are more likely to internalise stressful occurrences and experience psychological abuse [54], whereas males tend to express or act them out [55].…”
Section: Discussionsupporting
confidence: 91%
“…People living with HIV have a higher prevalence of suicidal ideation and suicide attempts than those without HIV [52]. Suicidal ideation is a predictive factor of suicide attempts and suicide death in people living with HIV [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatures suggested that cocaine has adverse effects Du et al 10.3389/fpsyg.2023.1125300 Frontiers in Psychology 12 frontiersin.org on HIV-associated neurocognitive disorder and neuro AIDS (Dahal et al, 2015;Illenberger et al, 2020). Additionally, several systematic reviews reported that substance abuse and depression are high risk factors for suicide in PLWH (Metekiya et al, 2022;Tsai et al, 2022). More research on the role of drug abuse (include cocaine, cannabis, and marijuana) in HIV infected individuals could contribute to the development of novel treatment strategies for PLWH with substance abuse.…”
Section: Cluster 4 Focus On Substance Abuse Associated With Hiv-relat...mentioning
confidence: 99%